Left Plueral Effusion: In Patients of Acute Necrotizing Pancreatitis - Abid Aziz, Muhammad; Bhatti, Tanvir Ahmad; Bhatti, Abdul Moiz; Ali, Khalid; Afzal, Muhammad; Uddin, Muhammad Aleem (Journal of Neonatal Surgery, 2025)
Background: Acute pancreatitis (AP) frequently progresses to pleural effusion (PE), the frequency of which varies considerably between research, and the link between PE and death is unclear. Objective: The objective of this research is to determine how often acute necritizing pancreatitis is accompanied by left plueral effusion. Methods: This Observational/ case series consisted of 74 patients. Patients with acute pancreatitis and serum amylase levels over 300U/dL were eligible. CT scans evaluated necrotizing pancreatitis prevalence, while chest X-rays assessed left plueral effusion. Complete data was analyzed using SPSS 22.0. Results: In 74 cases, 39 (52.7%) were males and 35 (47.3%) were females. The most common cause of acute pancreatitis was gallstones, followed by hypertriglyceridemia, alcoholism, medications, hypercalcemia and post ERCP. We found necrotizing pancreatitis in34 (45.9%) cases, and left plueral effusion was found in 31 (91.2%) cases. Among 34 cases of necrotizing pancreatitis 7 (20.6%) cases were died. Conclusion: We concluded that left pleural effusion in most necrotizing pancreatitis patients. Acute pancreatitis patients with high blood amylase levels and left pleural effusion must be treated early due to severe.